PENERAPAN SAHAM SERI A DWI WARNA PADA HOLDING BUMN PUPUK: Application of Series a Shares of Dwi Warna in The Holding of State-Owned Pupuk - MUNINGGAR, RORO AJENG (Jurnal Globalisasi Hukum., 2024)
The purpose of this scientific research is to analyze the implementation of Article 2A paragraph (2) of Government Regulation Number 72/2016 concerning the obligation for the State of Indonesia, especially to have special shares in subsidiaries of former SOEs. The State of the Republic of Indonesia c.q the Ministry of SOEs followed up PP 72/2016 by issuing a letter to the Fertilizer SOE Holding to assign shares with privileges to PT PKT, PT PKG, PT PKC, and PT PIM. The establishment of the Fertilizer SOE Holding itself was carried out based on PP 28/1997 and PP 54/2011. The normative research method uses the law as a source of approach and research material to obtain conclusions that are carried out with the deductive method. The results of this study explain that the transfer of the same owned by the State of the Republic of Indonesia to PT PKT, PT PKG, PT PKC, and PT PIM to the Fertilizer SOE Holding was carried out before the enactment of PP 2/2016 which took effect on the date of promulgation on December 31, 2016. Based on this, PT PKT, PT PKG, PT PKC, and PT PIM have no obligation to issue Series A Dwi Warna Shares as per Article 2A paragraph (2) PP 72/2016. This obligation applies to ex-BUMN companies whose transfer of shares of the State of Indonesia to SOEs occurs after the entry into force and promulgation of PP 72/2016. Also included is PT PSP which is an ex-spin off company